Overcoming Challenging Vascular Anatomy in Chronic Subdural Hematoma: Direct Carotid Bulb Access and Contralateral Middle Meningeal Artery Embolization - Patel, Saarang; Hoglund, Zachary; Palepu, Chandrasekhar; Scott, Kyle W.; Srinivasan, Visish M. (Journal of Neurological Surgery Reports, 2025)
Middle meningeal artery (MMA) embolization is an emerging intervention for subdural hemorrhage. Few cases discuss the utility of contralateral MMA embolization due to challenging ipsilateral MMA anatomy for this indication.A 90-year-old male presented after 6 days of slurred speech and severe headache. A head computed tomography (CT) revealed a left-sided 13-mm subdural hemorrhage, and neck CT angiography revealed left internal carotid artery stenosis at 50%. The carotid stenosis was treated with a standard carotid endarterectomy at the carotid bulb. Despite direct catheterization of the external carotid artery, selective catheterization of the MMA was not feasible. Instead, coils were placed in the left internal maxillary artery spanning the left MMA origin, and the right MMA was selectively embolized using a standard transradial approach. Postoperative CT showed a reduction in subdural hematoma (SDH) size, and the patient was discharged in stable condition on postoperative day 6.This case presents a rescue or salvage maneuver for MMA embolization for SDH with a favorable safety profile and outcome.
Keywords: neurosurgery; vascular; hematoma; carotid bulb access; middle meningeal artery embolization